Modeling and Simulating Bodies and Garments - Magnenat-Thalmann, Nadia; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Modeling and Simulating Bodies and Garments is a comprehensive visual textbook, dealing with all aspects of 3D virtual clothing and allowing users to try on virtual outfits. It covers a number of topics including: - Body modeling and animation - Character based adaptation - Cloth modeling and simulation - Design and animation of patterns and clothes - Virtual prototyping The chapters cover the complex issues that have to be addressed in order to successfully implement a 3D virtual try-on, discussing the adjustments that have to be made to calibrate the dimensions, the effects of motion, and cloth retargeting. The ultimate goal is for humans to see themselves at any time, wearing any clothing available in the database, adapted to their body size. Students and practitioners alike will benefit from the information contained in the book. Many images are included, and more can be found on www.miralab.ch.
Modeling Bodies -- Character Based Adaptation -- Cloth Modeling and Simulation -- Designing and Animating Patterns and Clothes -- Virtual Prototyping and Collaboration in the Clothing Industry.
Keywords: Computer science; Computer simulation; Computer graphics; Computer vision; Computer Science; Simulation and Modeling; Computer Graphics; Image Processing and Computer Vision